Acute lymphoblastic leukemia: an update on treatment and Brazilian perspective - Correa, Bruno Terra; Silva, Gabriela Sales Serra; Mendes, Webert Joaquim Silva; Soares, Laryssa Lopes; Lima, Joice Antunes; Pereira, Catarina Graziela Sousa; Souza, João Vitor Torquato de; Santos, Maria Eduarda Freire dos; Aleluia, Augusto Cezar Magalhães; da Guarda, Caroline Conceição; Póvoas, Regiana Quinto Souza; Gonçalves, Marilda de Souza; et al. (Frontiers in Oncology, 2026)
Acute lymphoblastic leukemia (ALL) is the most common pediatric cancer, representing a major global health concern, particularly in developing countries. This review provides an updated overview of the epidemiology, diagnosis, prognosis, treatment, and a Brazilian perspective for ALL. Despite advances in chemotherapy and immunotherapy, survival disparities remain challenging, driven by socioeconomic and healthcare access inequalities. Present diagnosis incorporates immunophenotyping, cytogenetics, and molecular biology for precise stratification and treatment planning. Treatment has evolved from monotherapy to multi-phase chemotherapy protocols, hematopoietic stem cell transplantation, monoclonal antibodies, and CAR T-cell therapy with risk-adapted strategies improving outcomes and offering hope in relapsed or refractory cases. However, these treatments remain largely inaccessible in low-to middle-income countries. Our review summarizes findings from Brazilian studies in children with ALL about diagnostics and treatment and highlights the importance of an accurate understanding of the national reality. Improved access to diagnostics, novel therapies, local multi-center studies, and pharmaceutical investment to enhance survival and quality of life for pediatric ALL patients is needed.